Evaluating the impact of non-medical m-health application: Towards development of a framework - Fadzillah, F.M. (Institute of Electrical and Electronics Engineers Inc., 2016)
Mobile applications (apps) to improve health especially in non-medical area are flourishing, but before a medical doctors can endorse an app to the patients, they need to know the impact of the apps and be assured that the app will be helpful to their patients. Thus, this study aimed to identify the criteria that are important for evaluating the impact of non-medical mobile health (m-health) apps. Based on the identified criteria and an in-depth literature review, a framework will be proposed. The framework which will be tested and validated in later stages of this research will be useful for developers, health providers and doctors as it act as guideline to identify the impact of using non-medical m-health apps. Â© 2016 IEEE.